Sinodalitas Gereja dan Aktualisasinya dalam Sikap dan Kepuasan Berlingkungan - Hermawan, Peter (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
In his address for the ceremony commemorating the 50th anniversary of the institution of the Synod of Bishops, Pope Francis said that synodality is a new way of church life in the third millennium. A synodal Church is formed by the communion of the people of God who are active and engaged in evangelization. Synodality is a manifestation of the Church as a communion of God's people and a pilgrimage of the Church in the world. With Synodality, both clergy and laity are invited to listen to the voice of the Holy Spirit through the sensus fidei, so that they can proclaim the Gospel to the world. Through the three main pillars of the Synodal Church, namely communion, participation, and mission, all the faithful are invited to listen to the Holy Spirit. The synodality of the Church cannot be separated from the parish circles because the parish circles are the foundation of the Church and support the life of the Church in its mission as salt and light. The parish circles are also a form of fellowship of the people of God. In addition, the parish circles from a management perspective are also a form of organization that cannot be separated from attitudes and organizational satisfaction. In the implementation of pastoral care in the parish circles, there are various attitudes and organizational satisfaction issues, such as parish circle administrators who are less proactive, encouraging the parish circle people to be active, disharmony between administrators and people in the parish circles, the tardiness in various parish circle activities, and the lack of young people who are interested in doing activities in the parish circles. With synodality in the parish circles, which is guided by the attitude of listening to each other sensus fidei, problems related to attitudes and organizational satisfaction in the parish circles are able to be resolved.